Oscillatory spectra of surface atoms in strongly anisotropic layered crystal (quasi-1D behaviour) - Feodosyev, S.B.; Gospodarev, I.A.; Gryshaev, A.V.; Gryshaev, V.I.; Mamalui, M.A.; Minaev, P.A.; Syrkin, E.S. (Condensed Matter Physics, 2000)
Vibrations localized near the surface have been analyzed using the Jacobian matrix method taking into account discreteness of the lattice. It has
been shown that localized surface vibrations in layered crystals have got
quasi-one-dimensional character and their properties are described by exact solutions obtained in the framework of the one-dimensional model. Коливання, що локалiзованi поблизу поверхнi, аналiзуються за допомогою методу J -матриць iз врахуванням дискретностi гратки. Показано, що в шаруватих кристалах такi коливання мають одновимiрний характер та можуть задовiльно описуватися за допомогою вiдповiдних точних аналiтичних виразiв, що отриманi для одновимiрної
моделi.